Adapting Active Support Interactive Training to a special school context to upskill classroom staff and increase engagement in pupils. (27th August 2021) - Evans, Ceridwen; Toogood, Sandy; Owen‐Leeds, Stephanie; Dwyfor, Leusa; Jorammanawar, Shabreen; Issa, Nour; Carl Hughes, J.
Abstract : Research indicates that engagement acts as an important precursor for learning, yet sustaining the engagement of pupils with special educational needs can be a challenge for classroom staff. An Active Support staff training package, Interactive Training, has been demonstrated as an effective way of increasing engagement in adults accessing learning disability services. In theory the logic of Active Support Interactive Training could extend to a school environment, with the aim of achieving similar outcomes. The current study evaluated a special school‐adapted version of Active Support Interactive Training with the aim of increasing engagement in pupils during group‐based learning. Findings showed an increase in engagement in pupils for all three settings (classrooms) immediately after intervention, which continued to either increase or stabilise at three‐month follow‐up. Further research could test the engagement behaviour of staff pre‐ and post‐ training intervention and explore practice leadership within the school leadership team to address maintenance.